Blood levels of nitric oxide and endothelin-1 in Helicobacter pylori-associated peptic ulcer in children - T.V. Sorokman; N.Ya. Cherney (Zaslavsky O.Yu., 2019)
Background. In recent years, many scientists emphasize the decisive role of the vascular wall in regulating the aggregate state of the blood, as well as the importance of its disorders in the development of digestive diseases. However, there are currently no data on the role of Helicobacter pylori in the development of endothelial dysfunction. The purpose was to evaluate the nature of nitric oxide (NO) and endothelin-1 changes in the blood of children with erosive-ulcerative lesions of the upper gastrointestinal tract. Materials and methods. Comprehensive clinical and instrumental-laboratory examination was performed in 120 children aged 7-18 years, 79 with chronic erosive gastroduodenitis and 41 with duodenal ulcer, as study group, and 50 children of the corresponding age without digestive diseases (control group). All children underwent a thorough clinical and paraclinical study according to methods generally accepted in the clinic. Concentration of nitrite in the blood plasma was determined by P.P. Golikov (2004). The study of endothelin-1 serum level was carried out by enzyme-linked immunosorbent assay using Biomedica Gruppe (Germany) sets. The results of the study are represented by the number of observations in the group, the percentage or the mean and the mean square deviation, the exact value of p. Results. Children were divided by age, sex, place of residence and nosological form of pathology. The level of NO in the blood plasma of children in the study group was significantly lower - 11.78 ± 1.10 μmol/l (p < 0.05). The intragroup analysis in both groups of examined children showed no significant difference in the blood content of NO (p > 0.05) depending on gender and age. In the absence of Helicobacter pylori, the level of NO in the blood is significantly higher compared to the group of patients diagnosed with Helicobacter pylori (p < 0.05). There is a difference in the levels of NO in the blood of children depending on the period of the disease: they are higher during the exacerbation, both chronic erosive gastroduodenitis and duodenal ulcer. On average, blood endothelin-1 level in patients of the study group was significantly lower than that of children in the comparison group (0.36 ± 0.02 fmol/ml and 0.48 ± 0.02 fmol/ml, respectively, p < 0.01). The level of endothelin-1 in the blood of children also depended on the presence of Helicobacter pylori. Conclusions. The levels of NO and endothelin-1 metabolites are significantly reduced in the blood of children with erosive and ulcerative pathology of the upper gastrointestinal tract, depend on the period of the disease, the presence of Helicobacter pylori and do not depend on age and gender.